Rapid electron transfer by the carbon matrix in natural pyrogenic carbon - Tianran Sun (Nature Portfolio, 2017)
Electron transfer reactions govern most biogeochemical processes, yet we have a limited knowledge of the electrochemistry of pyrogenic carbon, a major component of organic matter. Here, the authors quantify electron transfers between pyrogenic carbon and mineral phases under different pyrolysis temperatures.